2022
DOI: 10.1038/s41419-022-04764-2
|View full text |Cite
|
Sign up to set email alerts
|

HucMSC-derived exosomes delivered BECN1 induces ferroptosis of hepatic stellate cells via regulating the xCT/GPX4 axis

Abstract: Activated hepatic stellate cells (HSCs) are significant in liver fibrosis. Our past investigations have shown that human umbilical cord mesenchymal stem cells (hucMSCs) and their secreted exosomes (MSC-ex) could alleviate liver fibrosis via restraining HSCs activation. However, the mechanisms underlying the efficacy were not clear. Ferroptosis is a regulatory cell death caused by excessive lipid peroxidation, and it plays a vital role in the occurrence and development of liver fibrosis. In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…94 Notably, mesenchymal stem cell (MSC)exosomes alleviated liver fibrosis by triggering HSC ferroptosis mechanistically by promoting ferroptosis-like cell death, mitochondrial dysfunction, and lipid peroxidation in aHSCs. 95 In the future, the direct effect of HSC-derived exosomes on mitochondrial metabolism in HSCs should not be underestimated. The pathophysiological role of HSC-derived exosomes is summarized in Figure 1 and Table 1.…”
Section: Mitochondrial Metabolismmentioning
confidence: 99%
“…94 Notably, mesenchymal stem cell (MSC)exosomes alleviated liver fibrosis by triggering HSC ferroptosis mechanistically by promoting ferroptosis-like cell death, mitochondrial dysfunction, and lipid peroxidation in aHSCs. 95 In the future, the direct effect of HSC-derived exosomes on mitochondrial metabolism in HSCs should not be underestimated. The pathophysiological role of HSC-derived exosomes is summarized in Figure 1 and Table 1.…”
Section: Mitochondrial Metabolismmentioning
confidence: 99%
“…Mechanically, human UCMSC-Exs-derived BECN1 induced LX2 ferroptosis by reducing system xc-/GPX4 activity. In contrast, the knockdown of BECN1 weakened the effect of human UCMSC-Exs on LX2 ferroptosis [84]. The data demonstrate that MSCs ameliorate end-stage liver diseases via modulating liver cell ferroptosis.…”
Section: Mscs Regulate Cell Ferroptosismentioning
confidence: 77%
“…And due to the unique characteristics of exosomes, it is a natural intercellular communication vehicle with abundant functional cargo, which might be delivered to other cells and mediate key cellular process. For example, recent study demonstrated that hUCMSC-Exo cargo BECN1 could induce HSC ferroptosis to achieve hepatic fibrosis mitigation [ 46 ]. Wang N et.al found that miR-6766-3p in 3D-human embryonic stem cell exosome could target TGFβRII-SMADS pathway and inactivate HSC in liver fibrosis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%